2008
DOI: 10.1098/rspb.2008.0069
|View full text |Cite
|
Sign up to set email alerts
|

A community change in the algal endosymbionts of a scleractinian coral following a natural bleaching event: field evidence of acclimatization

Abstract: The symbiosis between reef-building corals and their algal endosymbionts (zooxanthellae of the genus Symbiodinium) is highly sensitive to temperature stress, which makes coral reefs vulnerable to climate change. Thermal tolerance in corals is known to be substantially linked to the type of zooxanthellae they harbour and, when multiple types are present, the relative abundance of types can be experimentally manipulated to increase the thermal limits of individual corals. Although the potential exists for this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
488
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(527 citation statements)
references
References 42 publications
18
488
7
3
Order By: Relevance
“…R. Soc. B 282: 20141725 particular conditions of disturbance and recovery, and that differences in these factors may explain variable reports of symbiont community stability or dynamism in the literature [8,9,[17][18][19][20][21][23][24][25][26]43]. Furthermore, these data illustrate that quantitative community metrics, rather than qualitative identification of the dominant symbiont, are necessary to evaluate symbiont shuffling responses.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…R. Soc. B 282: 20141725 particular conditions of disturbance and recovery, and that differences in these factors may explain variable reports of symbiont community stability or dynamism in the literature [8,9,[17][18][19][20][21][23][24][25][26]43]. Furthermore, these data illustrate that quantitative community metrics, rather than qualitative identification of the dominant symbiont, are necessary to evaluate symbiont shuffling responses.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, recovery with heat-tolerant symbionts can increase resistance to future thermal bleaching [8], but at a potential energetic cost [13][14][15][16]. Investigations of the ABH have revealed that, although corals sometimes change their symbionts [8,9,[17][18][19][20][21], this does not always occur: sometimes corals recover with the same symbiont community they had prior to stress [22][23][24][25][26]. These conflicting reports have generated controversy surrounding the ABH and the potential role of partner-switching in coral responses to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological and environmental parameters such as the history of thermal exposure and Symbiodinium-coral association (Baker 2003;Cooper et al 2011;Jones et al 2008;LaJeunesse et al 2010) may additionally impact the overall thermal stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated thermal stress may therefore result in a population with more heat-tolerant types of Symbiodinium (Jones et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Yet another strategy might be to host symbiont communities dominated by thermotolerant symbionts, either by the uptake of new symbionts after a bleaching event or by changing the relative abundance of symbiont types already present in the host (symbiont shuffling) (Baker, 2001;Baker et al, 2004;Berkelmans and van Oppen, 2006;Buddemeier and Fautin, 1993;Jones et al, 2008;Rowan et al, 1997). However, it is not yet established whether the observed acclimatisation will allow the corals to survive in the long run since only 23% of coral species may be able to change their symbionts (Goulet, 2006(Goulet, , 2007.…”
Section: Introductionmentioning
confidence: 99%